2008
DOI: 10.1387/ijdb.072350jk
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of cell polarity during cell cycle and oral replacement in Tetrahymena

Abstract: The aim of this study was to search for a mechanism responsible for the acquisition of cell polarity in a ciliate Tetrahymena. Homologs of the mammalian genes coding for CDC42-GSK3β-MARK/PAR1-MAPs proteins were found in the Tetrahymena genome (Eisen et al., 2006, and this study). These proteins belong to a pathway which controls assembly and disassembly of microtubule bundles and cell polarity in neural cells. In Tetrahymena, there are two types of morphogenesis: divisional and oral replacement (OR). In divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…According to the original authors, "The oral structures are missing often at 37°C, but present at 28°C" (154). More recently, this mutant was described as being "able to proliferate [in enriched medium at 37°C] yielding small cells with very variable phenotypes including some cells without oral apparatuses and some cells in OR [oral replacement] morphogenesis" (88). This strain was also sent to us, and we were unable to obtain progeny following crosses; we also found that the II8G cells produced silver-and protargol-stainable oral structures no matter how long the cells were kept at 39°C (Fig.…”
Section: The Mutationsmentioning
confidence: 99%
“…According to the original authors, "The oral structures are missing often at 37°C, but present at 28°C" (154). More recently, this mutant was described as being "able to proliferate [in enriched medium at 37°C] yielding small cells with very variable phenotypes including some cells without oral apparatuses and some cells in OR [oral replacement] morphogenesis" (88). This strain was also sent to us, and we were unable to obtain progeny following crosses; we also found that the II8G cells produced silver-and protargol-stainable oral structures no matter how long the cells were kept at 39°C (Fig.…”
Section: The Mutationsmentioning
confidence: 99%
“…However, there is the possibility that other kinases operate upstream of the Hippo pathway, for example creating a first wave of signaling required for the recruitment of the Hippo components to specific localizations. In Tetrahymena there are evidences that support the hypothesis that GSK3β (Glycogen synthase kinase 3s)-MARK/MAPs signaling pathway may be involved in the establishment of global cell polarity (Kaczanowska et al, 2008). Although Tetrahymena genome does not seem to encode the components of a Wnt signaling pathway, that operate upstream of this signaling, the orthologs of the GSK3β-MARK2/PAR-1 pathway were identified (Kaczanowska et al, 2008).…”
Section: The Cortical Inheritance Mechanismsmentioning
confidence: 99%
“…Noticeable is the fact that the guanine nucleotide exchanger Dock6 is simultaneously specific for the signaling of protein Rac1 and for the rho-type GTPase Cdc42. The GTPase Cdc42 is an essential conserved factor in controlling eukaryotic cell polarity that its encoded by a gene present in the genome of Tetrahymena (Miyamoto et al, 2007; Kaczanowska et al, 2008). Although it is uncertain if these complexes participate in Hippo signaling pathway, this shows that Mob1 regulation and activity is much more complex than previously predicted.…”
Section: The Cortical Inheritance Mechanismsmentioning
confidence: 99%
“…T. thermophila lacks orthologues of most of the Par network proteins, with the exception of CDC42 (TTHERM_00267910). Also, TTHERM_01017250 has weak similarity to PAR-1 (Kaczanowska et al, 2008). Despite the limited conservation of the Par network, the logic of cell polarization, based on cortical mutual cortical subdivision (right) in dividing cells grown at 39°C for 3.5 h. The numbers of scored cells are indicated.…”
Section: Evolutionary Conservation Of Cortical Antagonismmentioning
confidence: 99%